Accurate quantitation standards of glutathione via traceable sulfur measurement by inductively coupled plasma optical emission spectrometry and ion chromatography - L. Rastogi; K. Dash; J. Arunachalam (Elsevier, 2013)
The quantitative analysis of glutathione (GSH) is important in different fields like medicine, biology, and biotechnology. Accurate quantitative measurements of this analyte have been hampered by the lack of well characterized reference standards. The proposed procedure is intended to provide an accurate and definitive method for the quantitation of GSH for reference measurements. Measurement of the stoichiometrically existing sulfur content in purified GSH offers an approach for its quantitation and calibration through an appropriate characterized reference material (CRM) for sulfur would provide a methodology for the certification of GSH quantity, that is traceable to SI (International system of units). The inductively coupled plasma optical emission spectrometry (ICP-OES) approach negates the need for any sample digestion. The sulfur content of the purified GSH is quantitatively converted into sulfate ions by microwave-assisted UV digestion in the presence of hydrogen peroxide prior to ion chromatography (IC) measurements. The measurement of sulfur by ICP-OES and IC (as sulfate) using the âhigh performanceâ methodology could be useful for characterizing primary calibration standards and certified reference materials with low uncertainties. The relative expanded uncertainties (% U) expressed at 95% confidence interval for ICP-OES analyses varied from 0.1% to 0.3%, while in the case of IC, they were between 0.2% and 1.2%. The described methods are more suitable for characterizing primary calibration standards and certifying reference materials of GSH, than for routine measurements. Keywords: Glutathione, High performance methodology, MW-UV photolysis, Measurement uncertainty